American Legal Thought in Transatlantic Context, 1870-1914 - David M. Rabban (Clio@Themis, 2022)
Most American legal scholars have described their nineteenth-century predecessors as deductive formalists. In my recent book, Law’s History : American Legal Thought and the Transatlantic Turn to History, I demonstrate instead that the first generation of professional legal scholars in the United States, who wrote during the last three decades of the nineteenth century, viewed law as a historically based inductive science. They constituted a distinctive historical school of American jurisprudence that was superseded by the development of sociological jurisprudence in the early twentieth century. This article focuses on the transatlantic context, involving connections between European and American scholars, in which the historical school of American jurisprudence emerged, flourished, and eventually declined.